2018
DOI: 10.1111/mcn.12584
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood growth and cognitive outcomes: Findings from theMAL‐EDstudy

Abstract: Although many studies around the world hope to measure or improve developmental progress in children to promote community flourishing and productivity, growth is sometimes used as a surrogate because cognitive skills are more difficult to measure. Our objective was to assess how childhood measures of anthropometry correlate with measures of child development in low-income settings with high prevalence of poor nutrition and enteric disease, to inform studies considering growth outcomes in the absence of direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 48 publications
(59 reference statements)
9
45
2
1
Order By: Relevance
“…The child's height was assessed at the time of the study by measuring in centimetres and converted into an age referenced and standardized height‐for‐age z‐score (HAZ) using the World Health Organization's Anthro Plus software (version 3.2.2). In addition to HAZ, head circumference was also included as a risk factor that might be more specific to cognitive outcomes than HAZ (Scharf et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The child's height was assessed at the time of the study by measuring in centimetres and converted into an age referenced and standardized height‐for‐age z‐score (HAZ) using the World Health Organization's Anthro Plus software (version 3.2.2). In addition to HAZ, head circumference was also included as a risk factor that might be more specific to cognitive outcomes than HAZ (Scharf et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Organization's Anthro Plus software (version 3.2.2). In addition to HAZ, head circumference was also included as a risk factor that might be more specific to cognitive outcomes than HAZ (Scharf et al, 2018).…”
Section: Undernutritionmentioning
confidence: 99%
“…This is a commonly used assessment for early childhood and has been used in many research sites around the world. 6 31 …”
Section: Methods and Analysis (Standard Protocol Items For Randomisedmentioning
confidence: 99%
“…Children in Haydom followed in MAL-ED had a prevalence of stunting of 70% at 18 months of age. 5 Data from MAL-ED also showed that linear growth deficits correlated with lower scores for cognitive development, 6 potentially through shared barriers to optimal growth and brain development. 1 7 …”
Section: Introductionmentioning
confidence: 99%
“…As a secondary aim, we examined how growth and psychosocial risk factors relate to later development, as these factors have shown to be related to cognitive and sociobehavioral outcomes later in childhood (e.g. [18][19][20][21][22][23][24][25][26][27]).…”
Section: Introductionmentioning
confidence: 99%